(untitled) (Philological Studies, 2025)
After conducting a linguistic analysis, we came to the conclusion that the toponym Kumbor originates from Vulgar Latin cămpor(i/e) ’field’. This is confirmed, on the one hand, by the phonological analysis, and, on the other, by the comparative nominative analysis, which, only in the territory of the former Yugoslavia, reveals the existence of a large number of toponyms with the root polj-. The historical provenance data mentioned in the paper also generally support the theory that Kumbor originates from Vulgar Latin cămpor(i/e). The solution to the mystery of the etymology of the Kumbor toponym contributes not only to the enrichment of linguistic knowledge about the history of the b/c/h/s language, but also to the enrichment of knowledge about the social and cultural history of Boka Kotorska.